EXPLORING THE USE OF PHRASAL VERBS IN CELINE DION’S SONG LYRICS - Fania K, Ester; Mendrofa , Selviana; Yastanti, Unpris (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This research aims to analyze the use of phrasal verbs in five selected songs from The Best of Celine Dion album. The study focuses on identifying the types of phrasal verbs and interpreting their contextual meanings within the song lyrics. A descriptive qualitative method was applied with purposive sampling, selecting five songs: The Power of Love, To Love You More, My Heart Will Go on and on, Because You Loved Me, and Then You Look at Me. The collected phrasal verbs were classified based on their structure and grammatical functions, including transitive, intransitive, separable, and inseparable forms. The findings showed a total of 19 phrasal verbs used across the five songs. The Power of Love contained the highest number with 6 occurrences, while My Heart Will Go on and on had the fewest with only 2 occurrences. The phrasal verbs serve to enrich emotional expression in the lyrics, particularly in conveying themes such as loyalty, hope, love, and emotional support within a relationship. This study is expected to contribute to applied linguistic studies, especially in enhancing learners’ understanding of phrasal verb usage in authentic contexts such as song lyrics.